Organizing the Internal Manufacturing Complexity Elements in Adaptation of Current Manufacturing Environment: A Fuzzy Approach - Mohd Noor Hanif, M. R.; Wan Hasrulnizzam, W. H.; Musfirah, A. H.; Muhammad Ashlyzan, R.; Seri Rahayu, K. (College of Engineering, Universiti Teknologi MARA (UiTM), Malaysia, 2022)
Manufacturing industry has been developed outrageously during the past decade. The scenario also applies on Malaysian industry where 22.3% of the economy is generated from the manufacturing industry. Numerous latest concepts and technologies have been implemented by manufacturing firms to increase their productivity, product variety and efficiency. However, these changes also provide certain challenges by increasing manufacturing complexity and decreasing sustainability. Generally, manufacturing complexity is classified into internal and external complexity. This research intends to arrange the elements of internal manufacturing complexity (IMC) according to the priority through the period of enhancing sustainability. IMC elements were clustered into organizational, operational and productivity complexity. Fuzzy analytic hierarchical process was implemented in this research as multi criteria decision making method in IMC management.